ANALISIS ASUPAN PROTEIN DAN KALIUM TERHADAP STATUS GIZI BERDASARKAN SGA PASIEN GINJAL KRONIS DENGAN HEMODIALISIS - Listianasari, Yanita; Hardiantini, Dinni Annisa (Darussalam Nutrition Journal, 2025)
Background: Chronic kidney disease is a condition of progressive and irreversible decline in kidney function. CKD patients undergoing hemodialysis have a high protein requirement to replace proteins lost during the hemodialysis process and prevent hypermetabolisme caused by inflammation and infection. Adequate potassium intake is essential for CKD patients. Lack of potassium intake can have a negative impact on the body. Objectives: This research aims to analyze the relationship between protein and potassium intake and the nutritional status of chronic kidney patients with hemodialysis at the Tasikmalaya City Hospital, West Java. Methods: The type of research is an analytical survey with a cross-sectional study approach. Sampling was carried out by consecutive sampling, and 143 patients became respondents. Data on protein intake and potassium intake were obtained by interview using a 2 x 24 hour food recall form. Nutritional status data were obtained using the subjective global assessment (SGA) form. SGA is a screening method for determining the nutritional status of CKD patients with hemodialysis. Data processing and analysis using SPSS software. Results: There is a significant relationship between protein intake with a value of p= 0.001 (p<0.05) and potassium intake with a value of p= 0.003 (p<0.05) on the nutritional status of chronic kidney patients with hemodialysis. Conclusion: There is a significant relationship between protein and potassium intake and nutritional status.